Dynamic soft tissue mobilisation increases hamstring flexibility in healthy male subjects. Issue 9 (23rd August 2005) - Hopper, D; Deacon, S; Das, S; Jain, A; Riddell, D; Hall, T; Briffa, K
Abstract : Objectives: The purpose of this study was to investigate the effect of dynamic soft tissue mobilisation (STM) on hamstring flexibility in healthy male subjects. Methods: Forty five males volunteered to participate in a randomised, controlled single blind design study. Volunteers were randomised to either control, classic STM, or dynamic STM intervention. The control group was positioned prone for 5 min. The classic STM group received standard STM techniques performed in a neutral prone position for 5 min. The dynamic STM group received all elements of classic STM followed by distal to proximal longitudinal strokes performed during passive, active, and eccentric loading of the hamstring. Only specific areas of tissue tightness were treated during the dynamic phase. Hamstring flexibility was quantified as hip flexion angle (HFA) which was the difference between the total range of straight leg raise and the range of pelvic rotation. Pre- and post-testing was conducted for the subjects in each group. A one-way ANCOVA followed by pairwise post-hoc comparisons was used to determine whether change in HFA differed between groups. The α level was set at 0.05. Results: Increase in hamstring flexibility was significantly greater in the dynamic STM group than either the control or classic STM groups with mean (standard deviation) increase in degrees in the HFA measures of 4.7 (4.8), −0.04 (4.8), and 1.3 (3.8), respectively. Conclusions: Dynamic soft tissue mobilisation (STM) significantly increased hamstring flexibility in healthy male subjects.